2008
DOI: 10.1007/s00592-008-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

A fibrin gel carrier system for islet transplantation into kidney subcapsule

Abstract: Islet transplantation is a promising therapeutic option for type 1 diabetes, and actively performed in the clinic as well as in the animal experiments. For the rodent experiments, islet transplantation into kidney subcapsule is widely used to assess islet quality, however, it is often difficult to do using a polyethylene tubing and fine needle because of inherent dead volume of needle and stickiness of the tubing to islets. This problem makes it difficult to interpret the physiological response to different is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Of note, we considered retarded glucose control to be a major hurdle for the clinical application of fibrin as an islet vehicle. In the paper published by our colleague [23], fibrinislet composites transplanted underneath the kidney capsule achieved rapid glycemic control with a reduced islet mass. However, we experienced that the same protocol was not effective in the subcutaneous site, whose environment is highly hypoxic due to low vascularization potential (data not shown).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, we considered retarded glucose control to be a major hurdle for the clinical application of fibrin as an islet vehicle. In the paper published by our colleague [23], fibrinislet composites transplanted underneath the kidney capsule achieved rapid glycemic control with a reduced islet mass. However, we experienced that the same protocol was not effective in the subcutaneous site, whose environment is highly hypoxic due to low vascularization potential (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…In an in vitro three-dimensional culture system, fibrin glue was demonstrated to facilitate an increase of beta-cell mass while preserving normal function [21]. In preliminary studies, fibrin has been suggested to be a carrier for islet transplantation into the subcutaneous pocket [22,23]. However, major obstacle in the clinical application of fibrin as an islet carrier into the subcutaneous pocket is that there are no optimized protocols of the fibrin-islet composites in vivo to enable the implanted islets to achieve rapid glycemic control with a minimum amount of islets.…”
Section: Introductionmentioning
confidence: 98%
“…Encapsulating rat islets with fibrin, then transplanting them into diabetic nude mice normalized glycemia with a minimum of only 100 islet equivalents. 52 Another study found that transplantation of islets in a fibrin glue reduced diabetic mouse blood glucose to normal levels. 30 Our results show that human fetal pancreatic cells can be cultured with fibrin and transplanted to yield a successful graft.…”
Section: Discussionmentioning
confidence: 99%
“…136 Subcutaneous transplantation of fibrin-embedded islets was as effective as transplantation of free-floating islets under the kidney capsule in diabetic mice. 137 This study's results further support the notion that fibrin is an effective carrier.…”
Section: Fibrin Support Of Islet Cell Function Survival and Vasculatmentioning
confidence: 99%